Aviation industry in the system of national economy of the Republic of Kazakhstan (International relations and international law Journal, 2018)
In this article the Aviation branch in the system of national economy of the Republic of Kazakhstan is considered. Characteristic features of aviation branch of the Republic of Kazakhstan are analyzed. Over the years of independence, Kazakhstan has solved many problems in the field of civil aviation, significant progress has been made. The development of the industry does not stand still, the main goal remains unchanged, the implementation of which is focused on the activities of state programs and the efforts of aviation system employees-is to meet the needs of the economy and the population in air transportation, ensuring their safety and compliance with international standardsBased on this, we can say that the main principles for improving the air transportation market during the study were chosen: meeting the needs of the population and business communities of Kazakhstan and other States in air transportation; development of the market of cargo and passenger transportation within the country and abroad; improving the competitiveness of Kazakh air carriers and airports in the regional and global markets.Key words: aviation industry, system of national economy, significance, Republic of Kazakhstan.